2017
DOI: 10.17130/ijmeb.2017228684
|View full text |Cite
|
Sign up to set email alerts
|

Poli̇ti̇k İsti̇krarin/İsti̇krarsizliğin Ekonomi̇k Büyüme Üzeri̇ndeki̇ Etki̇leri̇: Dünyanin en Büyük İlk Yi̇rmi̇ Ekonomi̇si̇ Üzeri̇nde Bi̇r Uygulama (1996-2015)

Abstract: ÖZET Bu çalışmada, politik istikrarın/istikrarsızlığın ekonomik büyüme üzerindeki etkileri farklı politik rejim tiplerine sahip dünyanın en büyük ilk 20 ekonomisi üzerinde 1996-2015 dönemi için panel veri analiziyle incelenmektedir. Çalışmada, ekonomik açıdan gelişmiş G-12 ve gelişmekte olan G-8 ülkeleri olarak gruplandırılan bu 20 ekonominin gelişmişlik düzeylerinin farklılaşmasında politik istikrarın/istikrarsızlığın etkilerinin değerlendirilmesi amaçlanmaktadır. Çalışma sonucunda, inceleme döneminde G-12 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
1
1
0
2
Order By: Relevance
“…When assessed for the purpose of the study, it was determined that the countries had a negative impact on their economic growth performance. This finding obtained within the scope of the study is similar to the findings found in the studies conducted in the related literature (Barro, 1991;Alesina et al, 1996;Aisen and Veiga, 2006;Jong-A-Pin, 2006;Tang and Abosedra, 2014;Yalçınkaya andKaya, 2017 andKamacı 2019). In order to increase the economic growth performance in BRICS (Brazil, Russian Federation, India, China and South Africa) countries and Turkey, comprehensive policies should be determined and implemented to ensure and increase political stability, reduce inflation and reduce government expenditures according to the results of the analysis made within the scope of the study.…”
Section: Extended Abstractsupporting
confidence: 91%
“…When assessed for the purpose of the study, it was determined that the countries had a negative impact on their economic growth performance. This finding obtained within the scope of the study is similar to the findings found in the studies conducted in the related literature (Barro, 1991;Alesina et al, 1996;Aisen and Veiga, 2006;Jong-A-Pin, 2006;Tang and Abosedra, 2014;Yalçınkaya andKaya, 2017 andKamacı 2019). In order to increase the economic growth performance in BRICS (Brazil, Russian Federation, India, China and South Africa) countries and Turkey, comprehensive policies should be determined and implemented to ensure and increase political stability, reduce inflation and reduce government expenditures according to the results of the analysis made within the scope of the study.…”
Section: Extended Abstractsupporting
confidence: 91%
“…Political stability and environmental sustainability constantly influence each other. For the continuation of environmental sustainability, economic growth and ecological balance should be in harmony, and appropriate sustainable development policies should be prepared by taking the environmental factor into consideration when planning [3].…”
Section: Introductionmentioning
confidence: 99%
“…(Pesaran vd., 2008;Pesaran, 2004;Ünlü, 2022). Politik istikrar indeksi kurumsal olmayan ve/veya şiddet içeren yollarla hükümetin işlemez hale getirileceği veya devrilebileceği ihtimaline yönelik toplumun algısını ölçen alt göstergelerden oluşmaktadır (Kaufmann vd., 2010;Yalçınkaya ve Kaya, 2017). Buradan hareketle çalışmada elde edilen sonuçlar incelenen dönemde Avrupa Birliği üyesi 24 ülke ekonomileri için siyasal ve yönetimsel yapının belirlilik ortamını sağlayamadığı, kısmen istikrarsız bir yapıya sahip olduğu değerlendirilmektedir.…”
Section: Bulgularunclassified
“…;Yalçınkaya ve Kaya (2017),Tang ve Abosedra (2014) ve Jong-A-Pin (2006) politik istikrarın ekonomik büyüme üzerindeki etkisinin negatif olduğu sonucuna ulaşmışlardır. Bu çalışmalara karşıGür ve Akbulut (2012) veAlper (2018) ise politik istikrarsızlığın ekonomik büyüme üzerindeki etkisinin pozitif etkili olduğunu tespit etmişlerdir.Şanlısoy ve Kök (2006) veYiğit (2021) çalışmalarında politik istikrardan ekonomik büyüme doğru tek yönlü nedensellik ilişkisi olduğunu belirtmişlerdir.…”
unclassified